2012
DOI: 10.2478/v10239-012-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Some Chemical Properties of Sandy Soils Affected by Uncontrolled Dump Sites in the West Pomeranian Province

Abstract: WSTÊPNiekorzystny stan gospodarki odpadami w woj. zachodniopomorskim, wyra¿a siê m.in. nielegalnym pozbywaniem siê odpadów, w tym tak¿e odpadów niebezpiecznych, na niekontrolowanych (dzikich) wysypiskach. Siedem lat po wejciu do Unii Europejskiej Polska, mimo podjêtych zobowi¹zañ, nie spe³nia wymogów w zakresie redukcji iloci odpadów, budowy i utrzymania instalacji recyklingu i spalarni. W zwi¹zku z t¹ sytuacj¹ w latach 20102011 problematyka odpadów jest coraz czêciej omawiana w rodkach masowego przekazu (pras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to the literature (Malinowski et al 2012), the majority of uncontrolled landfills are found in Poland in light soils with the granulometric size of loose sand.…”
Section: Physical and Chemical Characteristics Of Soilsmentioning
confidence: 99%
“…According to the literature (Malinowski et al 2012), the majority of uncontrolled landfills are found in Poland in light soils with the granulometric size of loose sand.…”
Section: Physical and Chemical Characteristics Of Soilsmentioning
confidence: 99%
“…The samples were classified only as two grain size groups: sand and loamy sand (according to USDA). According to the literature (Malinowski et al 2012), the majority of illegal dump wastes are found in Poland in light soils with the granulometric size of loose sand, which contribute to the change of their properties, especially the chemical ones. Marking of the exchangeable and hydrolytic acidity allowed to determine the analyzed soil, which is in the acidic to alkaline range.…”
Section: Physical and Chemical Characteristics Of Soilsmentioning
confidence: 99%